Self-Development Strategies to Improve Interpersonal Relationships - Meity Meganita; Syafila Risqil Ubabah Ali; Allium Carissa Sativufany; Angeline Desrayamsi Hakim (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
Interpersonal relationships are how individuals interact and communicate between two or more people in an activity. Good interpersonal relationships will help and support individuals in making relationships with other people. The purpose of this research is to inform the public about self-development strategies that can improve interpersonal relationships. This article uses qualitative research methods with a literature review. From this article, we found that having good interpersonal relationship skills is very important in life. One of the key strategies for developing interpersonal relationships is effective communication. Therefore, interpersonal relationships cannot be separated from the personality that a person has.